2018
DOI: 10.7150/jca.25494
|View full text |Cite
|
Sign up to set email alerts
|

Overall survival and cancer-specific survival in patients with surgically resected pancreatic head adenocarcinoma: A competing risk nomogram analysis

Abstract: Background: The objective of this study was to estimate probabilities of overall survival (OS) and cancer-specific survival (CSS) in patients with pancreatic head adenocarcinoma after surgery. In addition, we attempted to build nomograms to predict prognosis of these patients.Methods: Patients diagnosed with surgically resected pancreatic head adenocarcinoma between 2004 and 2014 were selected for the study from the Surveillance, Epidemiology, and End Results (SEER) database. Nomograms were established for est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
47
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 32 publications
11
47
1
Order By: Relevance
“…To be noted, these studies only included with limited samples. A SEER-based study found the risk of cancer-specific death decreases with age in resectable PDAC patients (He et al, 2018). However, we found the age was not an independent prognostic factor for resectable PDAC patients.…”
Section: Discussioncontrasting
confidence: 68%
“…To be noted, these studies only included with limited samples. A SEER-based study found the risk of cancer-specific death decreases with age in resectable PDAC patients (He et al, 2018). However, we found the age was not an independent prognostic factor for resectable PDAC patients.…”
Section: Discussioncontrasting
confidence: 68%
“…The following classifications were confirmed: the International Classification of Diseases for Oncology, Third Edition (ICD-O-3), the histology code 8140 and the ICD-O-3 site code C23.9. The exclusion criteria have been described in a previous study (21), which mainly included (1) primary multiple tumors, (2) missing or incomplete information of follow-up, (3) pathologically confirmed not adenocarcinoma, (4) in-hospital or 30-day mortality after surgery, (5) American Society of Anesthesiologists (ASA) Physical Status 3 or above levels (14). Patients from the SEER dataset were randomly selected to serve as the training and internal validation cohorts in a ratio of 3:1.…”
Section: Patientsmentioning
confidence: 99%
“…Clinical and pathological variables, including age, gender, tumor size and grade, TNM stage, follow-up information, and cause of death, were collected and analyzed. Lymph node ratio (LNR) was defined and calculated according to our previous study (21). OS and CSS were defined as the duration from the date of diagnosis to the last follow-up or death due to all causes or GBC, respectively.…”
Section: Data Collectionmentioning
confidence: 99%
“…10 They demonstrated that both primary tumor location and diameter were significantly associated with the risk of synchronous liver metastasis. Tumor size, a powerful and reliable predictor of both distant metastasis and prognosis, 5,27 was found to have an intimate association with the infiltration of the pancreatic cancer cells into the liver. Larger size tumors were more invasive and infiltrated to the peripheral organs or vessels; which may also signify greater tumor burden for patients with PDAC.…”
Section: Discussionmentioning
confidence: 99%
“…3 Distant metastasis is a major indicator of poor prognosis. 4,5 PDAC predisposes the liver to secondary tumors and liver metastasis is the most common form of distant metastasis in these patients. 6 Also, it was shown that patients with liver metastasis had worse prognoses than those with lung metastasis or other distant metastases.…”
Section: Introductionmentioning
confidence: 99%